Letter : Voluntary industrial aid - Lyno, James
036-0037-001 ESTABLISHED MARCH 10th, 1866. REG.TRADE UNION No.193. REG. APPROVED No. 316. Amalgamated Society of WOOD-CUTTING MACHINISTS EXECUTIVE COUNCIL Telephone: ARDWICK 4012. Telegrams: WOODCUT, MANCHESTER General Secretary: JAMES LYNO. Registered Office: 32, MILTON STREET, MANCHESTER, 13. All Correspondence to be addressed to the General Secretary, JAMES LYNO. April 19th., 1937. JL/FC. Sir. W. Citrine, General Secretary, T.U.C. General Council, Transport House, Smith Square, London. S.W.1. Dear Sir, re Voluntary Industrial Aid I am in receipt of yours dated April 15th 1937, for which I thank you. I will, in accordance with your request, place same before my E.C. at their meeting to be held on April 24th 1937. Hoping this meets with your approval. Yours faithfully, James Lyno General Secretary. 292/946/36/37